2019
DOI: 10.1111/vco.12542
|View full text |Cite
|
Sign up to set email alerts
|

The canine RAD51 mutation leads to the attenuation of interaction with PALB2

Abstract: RAD51 forms a complex with BRCA2 and plays a central role in the DNA damage response pathway that is associated with homologous recombination. The structures of RAD51 and its homologues are highly conserved from prokaryotes to higher eukaryotes. Although a large number of BRCA2 mutations have been reported, there are only a few reports on the mutations of RAD51, which have been shown in humans and dogs. However, several mutations of canine RAD51 were identified from mammary gland tumour tissues in a recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 23,24 The deleted Q × 10 mutant coupled with the VP16 transactivation domain co‐transfected with 4 ng of pNL1.1[Nluc] Nluc reporter plasmid (Promega) containing 4 × GAL4 upstream activating sequences and 2 ng of pGL4.51 plasmid (Promega) into the HeLa and MDCK cells, which were purchased from ATCC, showed a significantly strong interaction with the LBD coupled with the GAL4 DBD domain; this was contrasted with the activities of the Q × 10 control in the mammalian two‐hybrid assay (MTH) with 1 nM DHT stimulation (Figure 2B,C). 25 However, the Q × 9, 11, and 12 variants did not show significant differences in their interactions with LBD compared with the Q × 10 control. A single glutamine fluctuation in the polyQ region in canine AR N‐terminals may not decisively affect the interaction between NTD and LBD.…”
Section: Figurementioning
confidence: 82%
“… 23,24 The deleted Q × 10 mutant coupled with the VP16 transactivation domain co‐transfected with 4 ng of pNL1.1[Nluc] Nluc reporter plasmid (Promega) containing 4 × GAL4 upstream activating sequences and 2 ng of pGL4.51 plasmid (Promega) into the HeLa and MDCK cells, which were purchased from ATCC, showed a significantly strong interaction with the LBD coupled with the GAL4 DBD domain; this was contrasted with the activities of the Q × 10 control in the mammalian two‐hybrid assay (MTH) with 1 nM DHT stimulation (Figure 2B,C). 25 However, the Q × 9, 11, and 12 variants did not show significant differences in their interactions with LBD compared with the Q × 10 control. A single glutamine fluctuation in the polyQ region in canine AR N‐terminals may not decisively affect the interaction between NTD and LBD.…”
Section: Figurementioning
confidence: 82%
“…HR is essential for DNA double‐strand break repair and cancer prevention (Hodgson & Turashvili, 2020 ; O'kane et al., 2017 ; Trenner & Sartori, 2019 ). Studies have shown a relationship between mutations in the BRCA2 (Borge et al., 2011 ; Enginler et al., 2014 ; Kaszak et al., 2018 ; Lüder Ripoli et al., 2016 ; Ozmen et al., 2017a ) and RAD51 genes and CMT (Canadas et al., 2018 ; Ozmen et al., 2017b ; Uemura et al., 2019 ). The significance of PALB2 mutations in BCs is well known and is routinely monitored (Cock‐Rada et al., 2018 ; Schroeder et al., 2015 ; Slavin et al., 2015 ; Yao et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A two‐hybrid assay indicated that the interaction of mutant type Rad51 with PALB2 was weaker than that of wild type Rad51. The conclusion was that RAD51 mutations affected oligomerization of the protein and that this could be the reason for its attenuated interaction with PALB2, which could promote cancer in dogs 49 …”
Section: Selected Ddr Proteins and Their Potential Role In Canine Res...mentioning
confidence: 99%
“…The conclusion was that RAD51 mutations affected oligomerization of the protein and that this could be the reason for its attenuated interaction with PALB2, which could promote cancer in dogs. 49 …”
Section: Selected Ddr Proteins and Their Potential...mentioning
confidence: 99%
See 1 more Smart Citation